Assessment the Mechanical Properties of Soil Cement Interlocking (SCI) Bricks: A Case Study in Malaysia - Ali A Mohammed (International Journal of Advances in Applied Sciences, 2012)
The research assessed and examined the mechanical properties of the Soil Cement Interlocking brick (SCI) to provide the information for the possible and appropriate development and revision of  the (SCI) brick due to the substantial benefits which can be obtained by improving these sorts of bricks .Therefore, drastic efforts and accurate attention were paid precisely on the laboratory tests .Some of the laboratory investigation on (SCI) bricks were conducted in conjunction  with the  use of various masonry standards to evaluate the Compressive Strength , Dimensional Tolerance ,Water Absorption , Initial Rate of Suction and Modulus of Rapture. Results illustrated that the water absorption for (SCI) brick ranged from (13.566% -17.045%) ,the Initial Rate of Suction ranged from (1.746-3.573) kg/m2 ,the compressive strength on the other hand fell in range between (7.733-12.33)N/mm2 for (SCI)bricks without mortar, whereas the compressive strength for (SCI)bricks filled with mortar ranged from (12.406-15.098)N\mm2  and Modulus of  Rapture was found to be to ranged between (0.004-0.023)Pa for (SCI) bricks without mortar ,whereas, Modulus of Rapture for (SCI)bricks filled with mortar was (0.004-0.017) Pa .The study revealed a good quality that can be produced from soil and cement by pressing method whereby contributing to sustainable development .